Technological prospecting: a study of technologies applied to cocoa processing and derivatives (Research, Society and Development, 2020)
This study aims to monitor patent-based sources of technological information. Subsequently, this study conducts a technology survey in a patent bank to identify: (i) the main patent filers; (ii) the depositor's profile; (iii) the number of patent filings in each country; and (iv) distribution by theme. The study used the national database of the National Institute of Industrial Property - INPI, and the ORBIT® software to build this mapping. As an exploratory research, the methodology used in this study was processed through the survey of bibliographic sources, data search, treatment and analysis of technological information accessible on patent basis, were investigated patents related to the technologies applied to processing and cocoa derivatives. The technological mapping showed evidence of technological routes related to the cocoa fermentation and drying process, which in turn is associated with the quality of almonds, which can add value to cocoa products, and will allow opening to new markets. Therefore, the discussions of this study become a relevant source of consultation, and may also help to better understand the way technological advances are being directed, and may also point out possible technological routes, giving subsidies for resource allocation and conducting research that is likely to generate economic, environmental and social value for the Southern Coastal Territory of Bahia.